EXPERIENCES AND CHALLENGES FACED BY FAMILIES DEALING WITH DELINQUENT CHILDREN IN BOTSWANA - Matlakele, Kenneth; Erasmus, Charlene (Social Work/Maatskaplike Werk, 2018)
Sexual abuse is not being reported adequately. Teachers are in an ideal position to deal with and report sexual abuse, but they are not sufficiently trained in this regard. Therefore it was necessary to evaluate whether training programmes could be effective. The research that informed this article focused on presenting a specific training programme to twenty primary school teachers after which two focus group interviews were conducted. The aim was to explore the participants’ perceptions regarding the programme. The teachers benefitted from the relevant information, they valued the group consolidation, they felt confident about sharing experiences and they were more prepared to act in sexual abuse cases.